Chronic management of pulmonary embolism in thromboangiitis obliterans. Issue 12 (13th December 2022) - Martinho, Mariana; Fonseca, Ana Glória; Calé, Rita; Pereira, Helder Horta
Abstract : Thromboangiitis obliterans (TAO), also known as Buerger's disease, is a rare small vessel vasculitis that is associated with an increased risk of arterial occlusion. Although venous thromboembolism has been described, the risk of its recurrence and the best long-term anticoagulation management is not known. Considering this, we would like to share our experience with two patients admitted to our hospital with recurrent pulmonary embolism and previous diagnosis of TAO, aiming to discuss the indication for indefinite anticoagulation in this population.